A Menu of Minimum Wage Variables for Evaluating Wages and Employment Effects : Evidence from Brazil - Sara Lemos (Institute for the Study of Labor (IZA), 2004)
The international literature on minimum wage greatly lacks empirical evidence from developing countries. Brazil?s minimum wage policy is a distinctive and central feature of the Brazilian economy. Not only are increases in the minimum wage large and frequent but the minimum wage has also been used as an anti-inflation policy in addition to its social role. This study estimates the effects of the minimum wage on both wages and employment using panel data techniques and Brazilian monthly household data from 1982 to 2000 at individual and regional levels. A number of conceptual and identification questions is discussed, for example: (1) Various strategies on how to best measure the effect of a constant (national) minimum wage are summarized in a ?menu? of minimum wage variables and used to estimate wage and employment effects. (2) An employment decomposition that separately estimates the effect of the minimum wage on hours worked and on the number of jobs is used. Robust results indicate that an increase in the minimum wage strongly compresses the wages distribution with moderately small adverse effects on employment.
Keywords: J38; 330; minimum wage; wage effect; employment effect; informal sector; public sector; Brazil; Mindestlohn; Lohnniveau; Beschäftigungseffekt; Brasilien